The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1002/mnfr.201600242
|View full text |Cite
|
Sign up to set email alerts
|

Subchronic treatment with grape-seed phenolics inhibits ghrelin production despite a short-term stimulation of ghrelin secretion produced by bitter-sensing flavanols

Abstract: The sustained satiating effects of GSPE are related to a long-term decrease in ghrelin expression. GA and oligomeric flavanols play a ghrelin-inhibiting role in this process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
33
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 53 publications
(89 reference statements)
2
33
0
Order By: Relevance
“…5 However, other effects might be mediated through interactions with the gastrointestinal tract where they act by inhibiting enzymes, 6 modulating inflammation and/or gut barrier properties, 7 or modulating enteroendocrine secretion. 8,9 The effects of flavonoids on gut microbiota have been recently reviewed; 7 but there are few studies analyzing the role of proanthocyanidins on gut microbiota which could also mediate their physiological effects.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…5 However, other effects might be mediated through interactions with the gastrointestinal tract where they act by inhibiting enzymes, 6 modulating inflammation and/or gut barrier properties, 7 or modulating enteroendocrine secretion. 8,9 The effects of flavonoids on gut microbiota have been recently reviewed; 7 but there are few studies analyzing the role of proanthocyanidins on gut microbiota which could also mediate their physiological effects.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly this treatment also increased energy expenditure, which together with reduced food intake led to a lower body weight gain. 8 The increased satiety has been linked to ghrelin secretion modulation, but whether other enterohomones are regulated in this specific treatment has not been shown. These results point out GSPE as an interesting candidate for ameliorating obesity and diabetes.…”
Section: Introductionmentioning
confidence: 99%
“…We ruled out the possibility that proanthocyanidins were playing an important role in inhibiting the gastrointestinal digestion process [14]. Remarkably, the animals ingested less food, which could be due to the changes induced by the extract on enteroendocrine signals (increased active GLP-1 [17] and decreased acylated ghrelin [18]) and/or by other signals that limit their need to feeding [17]. Bao et al, working with GSPE in diabetic rats and at doses similar to ours, also found an inhibition in food intake after chronic administration [19].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, as might be assumed, infused mice exhibit increased food consumption for 30 min after the treatment. 71 A number of human studies also reported differential effects of gastric stimulation by different bitter compounds. 69 Delayed gastric emptying, as well as the induction of conditioned taste aversion, has been observed after gastric denatonium benzoate infusion in rats, although blood hormone levels were not monitored in this study.…”
Section: Stomachmentioning
confidence: 99%
“…70 Another study in rats reported differential effects on ghrelin secretion depending on the duration (acute/ chronic) and type of bitter compound used, suggesting the existence of complex activity patterns between receptive molecules and bitter chemicals. 71 A number of human studies also reported differential effects of gastric stimulation by different bitter compounds.…”
Section: Stomachmentioning
confidence: 99%